Precancerous niche remodelling dictates nascent tumour persistence - G. Skrupskelyte; J. E. Rojo Arias; H. Ajith; Y. Dang; D. Rossetti; S. Han; M. K. S. Tang; M. T. Bejar; B. Colom; J. C. Fowler; K. Murai; W. Knight; et al. (Nature, 2026)
Abstract Interactions between mutant cells and their environment have a key role in determining cancer susceptibility 1–3 . However, understanding of how the precancerous microenvironment contributes to early tumorigenesis remains limited. Here we show that newly emerging tumours at their most incipient stages shape their microenvironment in a critical process that determines their survival. Analysis of nascent squamous tumours in the upper gastrointestinal tract of the mouse reveals that the stress response of early tumour cells instructs the underlying mesenchyme to form a supportive ‘precancerous niche’, which dictates the long-term outcome of epithelial lesions. Stimulated fibroblasts beneath emerging tumours activate a wound-healing response that triggers a marked remodelling of the underlying extracellular matrix, resulting in the formation of a fibronectin-rich stromal scaffold that promotes tumour growth. Functional heterotypic 3D culture assays and in vivo grafting experiments, combining carcinogen-free healthy epithelium and tumour-derived stroma, demonstrate that the precancerous niche alone is sufficient to confer tumour properties to normal epithelial cells. We propose a model in which both mutations and the stromal response to genetic stress together define the likelihood of early tumours to persist and progress towards more advanced disease stages.